Asset Quality and the Financial Performance of Commercial Banks in DRC (British Journal of Multidisciplinary and Advanced Studies, 2022)
This study aimed at assessing the impact of asset quality management on the financial performance of commercial banks in DR Congo from 2010 to 2020. This study had one specific objective which was to assess the relationship between the NPL and the performance of commercial banks in DR Congo. After analysis made by SPSS; After analysis the table n°3 shows that the asset quality as assessed by the NPLR has a negative impact on financial profitability because the return on assets decreases by 0.190 monetary units for every unit rise in nonperforming loans   (Y=-0,190x1+1,351 ). In actuality, a non-performing loan is a loss, and the higher it is, the less profitable it is. Since the sig value is 0.00, or less than 5%, the negative link between the two variables is statistically significant. Moreover, the NPLR had a negative impact on financial profitability (ROE), as the return on assets decreases by 1.717 units of money for every unit of money that the nonperforming loan increases (Y= -1,717x1+13,157)  . In actuality, a non-performing loan is a loss, and the higher it is, the less profitable it is. Since the sig value is 0.00, or less than 5%, the negative link between the NPL and ROE is statistically significant.